MENANAMKAN BUDAYA LITERASI PADA ANAK USIA DINI DI ERA DIGITAL - Imanda Fikri Aulinda (Universitas Negeri Makassar, 2020)
In today's digital era, society is facilitated by technological developments so that there is a lot of degradation of insight and knowledge due to a lack of literacy culture. A literacy culture that is not instilled from an early age results in a lack of children's interest in reading and writing. Cultivating literacy culture needs to be instilled from an early age, because at that age children enter a golden period or often called the golden age. Early childhood is a child aged zero to eight years, at that time children experience very rapid development and growth, so that the habits that children do from an early age will also become habits as adults.